2003
DOI: 10.1159/000074448
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Leptin on Leydig Cell Function of Normal and Hyperleptinemic Rats

Abstract: Neonatal L-monosodium glutamate (MSG) administration in rats induces several neuroendocrine and metabolic disruptions. Leptin, the adipocyte product, modulates several neuroendocrine systems including the hypothalamic-pituitary-gonadal (HPG) axis in mammals. The aim of the present study was to determine whether MSG-induced chronic hyperleptinemia could play any relevant role in the hypogonadism developed by male rats when examined in adulthood. We found that 120-day-old MSG male rats displayed significant hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…Elevated serum leptin in hypogonadal men (33,34) and elderly men (35) was shown to decrease during T replacement therapy. Giovambattista et al (36) suggested that leptin could affect both Leydig and Sertoli cells in the testis, but its direct effect might be only through Leydig cells. Ishikawa et al (24) showed that the ratio of leptin-immunostained germ cells to total germ cells was inversely correlated with serum T, sperm concentration, and Johnsen's score.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum leptin in hypogonadal men (33,34) and elderly men (35) was shown to decrease during T replacement therapy. Giovambattista et al (36) suggested that leptin could affect both Leydig and Sertoli cells in the testis, but its direct effect might be only through Leydig cells. Ishikawa et al (24) showed that the ratio of leptin-immunostained germ cells to total germ cells was inversely correlated with serum T, sperm concentration, and Johnsen's score.…”
Section: Discussionmentioning
confidence: 99%
“…In mice a lack of ghrelin does not affect fertility. While mice lacking ghrelin are fertile the mice lacking functional leptin (ob/ob) or with mutation of leptin receptor are obese, infertile, and exhibit impaired spermatogenesis [59][60][61][62][63]. In turn, experimental hyperghrelinemia in prepubertal male rats decreased serum LH and testosterone concentration and delayed timing of puberty [64].…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory action was independently confirmed using primary cultures of rat Leydig cells and the murine mLTC-1 clone from Leydig cell origin [53, 54]. The molecular basis for the inhibitory effects of leptin on testosterone secretion likely involves the decreased expression levels of the mRNAs encoding key steroidogenic factors, such as steroidogenic factor-1 (SF-1), steroid acute regulatory (StAR) protein, and P450 side-chain cleavage (P450scc) enzyme, but not of those of 17β-hydroxyl steroid dehydrogenase (17β-HSD) type III [55].…”
Section: Roles Of Leptin In the Control Of The Hpg Axismentioning
confidence: 87%